Analysis of the Neurologic Deficit under the Traumatic Brain Injury and Methods of Its Correction - S. V. Ziablitsev; O. O. Starodubska; S. L. Bogza (Kazimierz Wielki University, 2017)
Objective of the research. Provide the analysis of the neurologic deficit in dynamics under the experimental traumatic brain injury and methods of its correction by Carbacetam. Materials and the methods of research. The research was held by means of the white outbred male rats, aged six months, weighing 180-220 g, which were kept on a standard diet with free access to food and water in vivarium conditions. The modulation of the traumatic brain injury was based on the method of V.M. Eslki and S.V. Ziablitsev (2005), where the TBI was caused due to gravity load on animals' fixed heads. The process was held in compliance with the Helsinki Declaration adopted by the General Assembly of the World Medical Association, the general rules and principles of the European Convention for the Protection of Vertebrate Animals. The rats of experimental group 1 and 2 were analyzed based on the impact of Carbacetam and Actovegine onto TBI provided in recommended therapeutic dozes, i.e. intraperitoneally at a dose of 5 mg and 16 mg per kilogram of animal accordingly during 7 days. The comparison group consisted of the rats that were treated by the same manipulations as the above-mentioned experimental groups; however, 1 ml of saline was administered intraperitoneally instead of the experimental medicines. The following indicators were analyzed in 24 h, three days and a week based on 100 score scale: level of consciousness; status of reflex area, including the width and the reaction of pupils to light, corneal reflex, hearing, muscle tone of the body and the reaction to light and pain; breath; movements and some behavioral reactions. Outcomes and conclusions. The data received pointed to moderate but feasible recovery of the neurological symptoms of rats under Carbatsetam in three days and a week of treatment in the reflex area, behavior and consciousness. Actovegine had significantly greater effect against the action of Carbatsetam in the motoric area. This can be used in the development of guidelines for the treatment and rehabilitation of the patients suffering TBI, depending on the scope of the major neurological disorders.